2012
DOI: 10.1007/s13224-012-0166-4
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Intravenous Iron Sucrose in Management of Iron-Deficient Anemia of Pregnancy at Rural Hospital Set Up

Abstract: Objectives Critical evaluation of iron sucrose (Malhotra, FOGSI Focus 9-11, 2009) in terms of efficacy, safety, and feasibility at rural setup for the treatment of anemia of pregnancy (Raja et al., Rawal Med J 28: 40-3, 2003) along with any reduction in blood transfusion rate at peripartum period of 37 weeks to 48 h within delivery. Methods In a prospective cohort study conducted in Department of Obstetrics and Gynaecology, during the year 2008 AVBRH-Wardha, 256 consecutive women of irondeficient anemia (IDA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 4 publications
2
15
0
Order By: Relevance
“…Direct comparison of our findings with other available published information is difficult on account of differences in inclusion criteria, target Hb level, allowance made for iron store repletion, and time of endline Hb measurement. [ 11 12 13 14 15 16 17 18 ] Nonetheless, our finding is well within the range of reported increase in Hb level of 1.6 g/dL to 3.6 g/dL. [ 11 12 13 14 15 16 17 18 ]…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Direct comparison of our findings with other available published information is difficult on account of differences in inclusion criteria, target Hb level, allowance made for iron store repletion, and time of endline Hb measurement. [ 11 12 13 14 15 16 17 18 ] Nonetheless, our finding is well within the range of reported increase in Hb level of 1.6 g/dL to 3.6 g/dL. [ 11 12 13 14 15 16 17 18 ]…”
Section: Discussionsupporting
confidence: 89%
“…[ 14 ] In most of the published literature, an additional amount of 500 mg of iron was added to the calculated iron deficit for replenishing body iron reserve. [ 11 12 15 17 18 ] The maximum increase in Hb level (3.6 g/dL) was seen in a study that had added 1000 mg of iron for replenishment of iron store. [ 14 ] In our study, only 16.4% of moderately anemic pregnant women became nonanemic after receiving IVIS, and more than half (57.8%) of them remained in the same category even after receiving IVIS in recommended dose.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of studies involved a comparison group of some kind including oral iron (n = 17; 36%), 11,14,16,19,24,26,27,29,31,32,34,35,37,39,50,56,57 IV iron (n = 4; 9%), 13 [14][15][16]18,20,24,26,28,31,[33][34][35][36][37][38][39]41,42,44,49,50,53 Only one study was identified that directly compared the administration of a full replacement dose of IV iron to a dose that was 300 mg less than the calculated full replacement dose. In comparing the two groups, administration of the full replacement dose was associated with a greater increase of 8 g/L 3-4 weeks after administration and 14 g/L at delivery.…”
Section: Overview Of Included Studiesmentioning
confidence: 99%
“…The prevalence of moderate or severe adverse reactions requiring treatment or discontinuation of IV iron was slightly higher in observational studies (13/1352; 9.6 per 1000 women; n = 20 studies) 12,13,19,20,22,23,32,33,40,41,44- [11][12][13][14][15][16]19,20,[22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][44][45][46][47][49][50][51] or FCM (1/276; 3.6 per 1000).…”
Section: 38mentioning
confidence: 99%
“…Shrivastava et al [26] reported significant progressive increases in Hb conc. with 3 weeks of intravenous IS therapy with a decline in the rate of blood transfusion among total anemic women in the peripartum period in rural areas.…”
Section: O Group IV Groupmentioning
confidence: 99%